Characterization of the Microstructural and Mechanical Properties of MoZrN Coating - Abboudi, Abdelaziz; Chermime, Brahim; Djebaili, Hamid; Brioua, Mourad (Journal of Nano- and Electronic Physics, 2017)
The aim of this paper is evaluation of properties of samples with The ternary nitride (Mo,Zr)N thin films were grown on silicon and steel XC100 substrates by the reactive RF magnetron sputtering technique. The substrates were exposed to ion bombardmen coating, which was deposited on two types of substrates. Silicon was made by melt technology, this method belongs to PVD (Physical Vapour deposition) process. Thin PVD coatings deposited onto surface of tools and machine parts are widely used in a range of sectors, for example in machine engineering. These materials, wear resistance and thermal and chemical stability of the surface. Structure, chemical composition a properties of thin layers depend on technological parameters of the PVD process and preparation of steel substrate. High requirements on the quality of thin PVD coatings resulted in development of methods used to evaluate of their properties. The theckness is one of the important characteristics of mechanical properties of the coated parts. The surface morphology, microstructure, and composition were studied by atomic force microscopy (AFM) nanoindentation, scanning electron microscopy (SEM) and X-ray diffractometer.